Properties Related to Weight Function - Parajuli, Vinod; Ghimire, Santosh (Journal of Advanced College of Engineering and Management, 2018)
In this paper, we begin with brief discussion of theory of weights and Ap weight functions. We then state and prove some of the properties of AP weight function using elementary analysis tools. Journal of Advanced College of Engineering and Management, Vol. 3, 2017, Page: 111-114